SENSITIVITY ISOLATE ESCHERICHIA COLI PATHOGEN OF BROILER ORGANS THAT INFECTED COLISEPTICAEMIA AGAINTS - Luhung, Yusmaniar Galuh Adi; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
This study aims to determine the sensitivity pattern pathogenic E. coli against antibiotics: oxytetracycline, ampicillin and sulfamethoxazole, in broilers in the Mangesta Village, Penebel, Tabanan Regency. The samples used in this research were 15 samples of colisepticaemia infected broiler’s organs . Sampels were isolated on media EMBA then identified with a Gram staining and biochemical tests with a TSIA, SIM, SCA and MRVP. Positive isolates of the bacterium E. coli were tested sensitivity to antibiotics oxytetracycline, ampicillin and sulfamethoxazole. The results showed that the sensitivity test of E. coli bacteria were isolated from the organs broilers suffered from colisepticaemia : 73.3% of E. coli resistant, 20% intermediate, and 6.7% was sensitive to the antibiotic oxytetracycline, 100% resistant to the antibiotic ampicillin, 53.3% and 46.7% intermediate resistance against sulphamethoxazole.
Keywords: ayam pedaging, E. coli, koliseptikemia, oksitetrasiklin, ampisilin, sulfametoksasol.